Український центр народної культури “Музей Івана Гончара” - Гуць, М. (Народна творчість та етнографія, 2007)
The article is dedicated to research of Ukrainian Center of National Culture Ivan Honchar Museum. The author of the article describes the history of this monument and gives detailed description of the stuff of the museum. Also the author focuses on folklore activity of the museum.